To evaluate the function \( f(x) = 4x + 3 \) for the various values of \( x \), we will substitute each value into the function.
(a) To find \( f(5) \): \[ f(5) = 4(5) + 3 = 20 + 3 = 23 \]
(b) To find \( f(0) \): \[ f(0) = 4(0) + 3 = 0 + 3 = 3 \]
(c) To find \( f(-7) \): \[ f(-7) = 4(-7) + 3 = -28 + 3 = -25 \]
(d) To find \( f\left(\frac{1}{2}\right) \): \[ f\left(\frac{1}{2}\right) = 4\left(\frac{1}{2}\right) + 3 = 2 + 3 = 5 \]
(e) To find \( f\left(-\frac{1}{5}\right) \): \[ f\left(-\frac{1}{5}\right) = 4\left(-\frac{1}{5}\right) + 3 = -\frac{4}{5} + 3 = -\frac{4}{5} + \frac{15}{5} = \frac{11}{5} \]
In summary:
- \( f(5) = 23 \)
- \( f(0) = 3 \)
- \( f(-7) = -25 \)
- \( f\left(\frac{1}{2}\right) = 5 \)
- \( f\left(-\frac{1}{5}\right) = \frac{11}{5} \)